Therapy‐related myeloid neoplasms with normal karyotype show distinct genomic and clinical characteristics compared to their counterparts with abnormal karyotype. (18th March 2022) - Tariq, Hamza; Barnea Slonim, Liron; Coty Fattal, Zachary; Alikhan, Mir B.; Segal, Jeremy; Gurbuxani, Sandeep; Helenowski, Irene B.; Zhang, Hui; Sukhanova, Madina; Lu, Xinyan; Altman, Jessica K.; Chen, Qing C.; et al.
Summary: Therapy‐related myeloid neoplasms (t‐MNs) are a complication of treatment with cytotoxic chemotherapy and/or radiation therapy. The majority of t‐MNs show chromosomal abnormalities associated with myelodysplastic syndrome (MDS) or KMT2A rearrangements and are characterized by poor clinical outcomes. A small but substantial subset of patients have normal karyotype (NK) and their clinical characteristics and mutational profiles are not well studied. We retrospectively studied patients diagnosed with t‐MN at three institutions and compared the mutational profile and survival data between t‐MNs with NK and t‐MNs with abnormal karyotype (AK). A total of 204 patients with t‐MN were identified including 158 with AK and 46 with NK. NK t‐MNs, compared to AK, were enriched for mutations in TET2 ( p < 0.0001), NPM1 ( p < 0.0001), ASXL1 ( p = 0.0003), SRSF2 ( p < 0.0001), RUNX1 ( p = 0.0336) and STAG2 ( p = 0.0099) and showed a significantly lower frequency of TP53 mutations ( p < 0.0001). Overall survival (OS) was significantly lower in AK t‐MNs as compared to NK cases ( p = 0.0094). In our study, NK t‐MNs showed a significantly better OS, a higher prevalence of MN‐associated mutations and a lower frequency of TP53 mutations compared to their AK counterparts. The distinct clinical and mutational profile of NK t‐MNs merits a separate classification.